2021
DOI: 10.16899/jcm.949763
|View full text |Cite
|
Sign up to set email alerts
|

Sistemik İsotretinoin Tedavisi Alan Akne Vulgaris Hastalarında Nötrofil- Lenfosit Oranı ve C-Reaktif Protein Düzeyleri

Abstract: Introduction: Inflammatory mediators have importance in acne vulgaris pathogenesis. Which mediators cause lesions or increase with which variants is not clear. Neutrophil-lymphocyte ratio and C-reactive protein are the inflammatory indicators that used for follow up of inflammatory diseases. There are various studies state that neutrophil-lymphocyte ratio and C-reactive protein levels are important for systemic isotretinoin treatment or not. Evaluation of changes in neutrophil-lymphocyte ratio and C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a study, patients using oral isotretinoin showed a significant decrease with treatment. 33 In another study, there was no statistical difference in CRP values after 4 months of oral isotretinoin treatment. 34 However, there was a study showing a significant increase in CRP levels with 6 months of oral isotretinoin treatment.…”
Section: Cosansu Et Al Retrospectively Investigated the Anti-inflamma...mentioning
confidence: 92%
“…In a study, patients using oral isotretinoin showed a significant decrease with treatment. 33 In another study, there was no statistical difference in CRP values after 4 months of oral isotretinoin treatment. 34 However, there was a study showing a significant increase in CRP levels with 6 months of oral isotretinoin treatment.…”
Section: Cosansu Et Al Retrospectively Investigated the Anti-inflamma...mentioning
confidence: 92%